Feeder Pig Nursery Cost Return Projection - Dhuyvetter, Kevin C.; Tokach, Mike D.; Dritz, Steve S.; DeRouchey, Joel; Tonsor, Glynn T. (My University, 2011)
This publication provides estimated cost and returns for a feeder pig nursery.
MF2151_2011_01
Keywords: MF2151; Livestock; Economics; MF